Soft skills as key competences for successful employability of graduate students - Amalia L. Kuregyan; Mariya A. Khusainova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In modern world, the higher vocational education system must not only be able to promptly respond to the changing demands of different industries for specialists of the required majors, but also to facilitate their rapid employment. Graduates employability is an increasingly important issue. In addition to basic academic and vocational training, graduates are also required to possess flexible skills that are pivotal in transitioning from education to employment. So, for a successful activity, any specialist needs two categories of skills: hard and soft skills. When talking about hard skills, technical knowledge is meant. On the opposite, soft skills refer to communication, team work, creativity, problem solving and other personal skills. Experts agree that beside hard (technical) skills, soft (non-cognitive) skills are necessary. They represent psychological attributes that inform how people learn, think, and act. Measuring soft skills is important because they are variables that allow students to predict their professional future and career orientation. This paper presents the results of studies which have been conducted to identify key competences which todays graduates should have in order to get a desired job. Main methods and techniques that help to master and improve them are also discussed.